A Case Study of Co-production Within a Mental Health Recovery College Dementia Course: Perspectives of A Person With Dementia, Their Family Supporter and Mental Health Staff - West, Juniper; Birt, Linda; Wilson, Danielle; Mathie, Elspeth; Poland, Fiona (Frontiers in Rehabilitation Sciences, 2022)
Background Undertaking co-production as a power-sharing way to improve mental health dementia services remains uncommon, suggesting opportunities to apply knowledge from lived experience of people with dementia, may often be missed. One barrier is stigma, assuming people with progressive cognitive impairment cannot manage this level of participation, support peers nor offer a “valid” perspective. Purpose This paper shares knowledge gained from a service evaluation that explored various experiences of a person with dementia, their family supporter and mental health staff, involved in co-producing a course about “living well” with dementia, within a mental health Recovery College. Design A qualitative, case study approach used semi-structured interviewing and inductive thematic analysis. Findings Co-production activities generated a shared sense of positivity, pride and privilege, highlighting positive effects in breaking down the “them and us” barriers common in traditional healthcare professional-service user relationships. Each individual had both something to offer and something to gain during the process. Staff identified challenges in the co-production process; in that balancing all the voices during meetings could be complex at times, and the process overall required considerable time commitment. Conclusion Taking part in co-production at an appropriate level and with peer support is a relational activity seen to be valuable in powerfully, yet gently, challenging stigma and assumptions around dementia. Findings show that while the process of co-production requires time and dedication, there is overall value in involving people living with dementia both in co-production and in peer support. This provided a straightforward and beneficial means to inclusively improve post-diagnosis support and care quality within a memory service.